PANDEMI COVID-19 SUATU TANTANGAN KETAATAN REMAJA KRISTEN PADA PROTOKOL KESEHATAN - Lydia Weniati Augustiana; Amos Neolaka; Maya Malau (Didache: Jurnal Teologi dan Pendidikan Kristen, 2021)
The purpose of the study was to determine the obedience of the community, especially Christian adolescents, in the health protocol (prokes). The problem is the obedience of Christian adolescents in the Prokes, as the government's appeal to end Pandemic Covid-19. The method is a digital literature study. Data collection techniques through journal and e-book studies on adolescent obedience in health protocol and the impact of the Covid-19 pandemic, which results in PPKM. Data analysis is descriptive qualitative with a matrix approach. The results of the study are (1) of adolescent disobedience in prokes is quite high: hand washing 51.7%; Wear a 60.3% mask; Maintain a distance of 93.1%. (2) Needed parent assistance in his teenage children at Pandemic Covid-19. (3) Featuring Pak at home when Pandemic Covid-19 is needed for the growth of adolescent faith. (4) The anxiety of Christian teenagers in the Pandemic Covid-19 time includes a light category, because they have knowledge of Covid-19, good relations with the family and a good level of faith growth. (5) The development of the spirit of elementary school children in the Pandemic Covid-19 period, increasing because children often follow prayers, worship, and discussions with parents while being confined at home. (6) the activities of the sizes (thank God) are very meaningful to reduce the symptoms of depression, stress, anxiety and loneliness of students. Therefore, educators need to provide assistance with efforts to reduce learning or lectures to students, so students are able to maintain emotional stability and can control depression, anxiety, stress and lonely symptoms.    Tujuan penelitian adalah untuk mengetahui ketaatan masyarakat khususnya remaja Kristen pada protokol kesehatan (prokes). Permasalahan adalah ketaatan remaja Kristen pada prokes, sebagai himbauan pemerintah mengakhiri pandemi Covid 19. Metodenya adalah studi pustaka digital. Teknik pengumpulan data melalui kajian jurnal dan e-book tentang ketaatan remaja pada protocol kesehatan dan dampak pandemi Covid-19 yang mengakibatkan PPKM. Analisis data adalah kualitatif deskriptif dengan pendekatan matriks. Hasil penelitian adalah (1) Ketidaktaatan remaja pada prokes cukup tinggi: mencuci tangan 51,7%; memakai masker 60,3%; menjaga jarak 93,1%. (2) Dibutuhkan pendampingan orangtua pada anak remajanya di saat pandemic Covid-19. (3) Pengajaraan PAK di rumah saat pandemic Covid-19 sangat dibutuhkan untuk pertumbuhan iman remaja. (4) Kecemasan remaja Kristen di masa pandemic Covid-19 termasuk kategori ringan, karena mereka memiliki pengetahuan tentang Covid-19, hubungan baik dengan keluarga dan tingkat pertumbuhan iman yang baik.  (5) Perkembangan spiritulitas anak usia SD di masa pandemic Covid-19, makin meningkat karena anak sering mengikuti doa, ibadah, dan diskusi bersama orangtua selama terkurung di rumah. (6) Kegiatan kebersyukuran (mengucap syukur pada Tuhan) sangat bermakna untuk menurunkan gejala depresi, stress, kecemasan dan kesepian peserta didik. Karena itu tenaga pendidik perlu memberikan pendampingan dengan upaya penurunan beban belajar/perkuliahan kepada peserta didik, agar peserta didik mampu menjaga stabilitas emosi dan dapat mengendalikan depresi, kecemasan, stress dan gejala kesepian.